A new approach to the surveillance of patients with changes in the mucous membrane of the cervix associated with human papillomavirus - I. A. Kuznetsova; N. M. Shakhova; L. D. Andosova; M. B. Karabut; Ye. E. Yunusova; O. V. Kachalina (Опухоли женской репродуктивной системы)
The article presents the results of prospective, controllable, randomized research the purpose of which was examination of opportunities of optical coherent tomography using diagnostic monitoring of patients suffering from human papillomavirus associated changes of cervical mucous in low degree. There were 50 patients examined of basic and control groups with dynamic observation during 3 years. It was determined that inclusion of optical coherent tomography in diagnostic algorithm allowed to reduce the amount of ungrounded biopsies by 39 % and to decrease the frequency of instrumental and laboratory methods of monitoring.